Residual stresses and martensite transformation in AISI 304 austenitic stainless steel. (3rd October 2018) - Deng, X T; Cheng, M; Zhang, S H; Song, H W; Taha, Mohamed Adel
Abstract: The present work aims at evaluation of the correlation between residual stresses and strain-induced martensitic transformations in AISI 304 austenitic stainless steel during deformation by x-ray diffraction. Moreover, investigating the effects of strain rate, temperature, and degree of deformation on the tensile properties, residual stresses, and martensitic transformation. Thus, uniaxial tensile tests were carried out at room temperature and 150 °C with different stress states. The experimental results showed clearly the dependency of residual stresses on the martensite volume fraction. Furthermore, it was observed that the residual stresses and martensitic transformations decreased with increasing strain rate and temperature. The residual stress value was always higher near to the tensile fracture surface. Additionally, it was increased with increasing of the deformation degree.